ANALISIS HUMAN ERROR TERHADAP KESEHATAN DAN KESELAMATAN KERJA PEKERJA LOGAM DAN PERMESINAN PADA PROSES PRODUKSI MENGGUNAKAN PENDEKATAN HEART STUDI KASUS CV ANDHY KARYA - Lutfi, Lutfi; Yuamita, Ferida (Universitas Muhammadiyah Gresik, 2023)
The production process of CV Andhy Karya goes through several production lines, starting from the printing process, casting process, machining and finishing process. The work accident report for 2023 shows that as many as 20% of 30 workers have serious work accidents in the casting and machining process. Occurs during the casting process where the worker's foot is exposed to a hot metal liquid during casting which results in the worker's leg suffering serious burns and being referred to the hospital. Based on the above events, to minimize the occurrence of work accidents and human error, the purpose of this study is to identify and measure human error probability then determine control efforts to minimize the occurrence of human error on occupational safety and health. . The results of this study show. The task with the highest human error probability value in the printing and casting process is task 2.2 to enter raw materials into the combustion furnace, HEP value of 0.283. In the machining process, the task with the highest HEP value is task 1.2, turning on and adjusting the lathe with a HEP value of 0.320. In the finishing process of the task, the highest HEP value, task 1.1, moves the product from the grinding place to the painting place with a HEP value of 0.150. Efforts for control can be done by using stairs with the correct procedures, providing handles on stairs, using anti-slip footwear and not carrying excessive loads. Use PPE (gloves), follow safety procedures recommended by the machine, and maintain concentration in work. Then workers can lift products with a weight that is not excessive and lift products with the help of other tools or not manually such as using a trolly.